2012
DOI: 10.1099/jmm.0.035154-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus acidophilus KFRI342 on the development of chemically induced precancerous growths in the rat colon

Abstract: Lactobacillus acidophilus KFRI342, isolated from the Korean traditional food kimchi, was investigated for its suitability as a dietary probiotic. The effects of L. acidophilus KFRI342 on the development of chemically induced (1,2-dimethylhydrazine; DMH) precancerous cytological changes of the colon were investigated in rats. Forty-five male F344 rats were randomly divided into three dietary groups. The control group received a high-fat diet (HF), a second group received a high-fat diet containing the carcinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Several studies showed the ability of numerous strains belonging to species L. acidophilus, L. casei and L. rhamnosus to either prevent or inhibit ACF formation (Rao, Sanders, Indranie, Simi, & Reddy, 1999;Verma & Shukla, 2013b). For instance Chang, Shim, Cha, Reaney, and Chee (2012) showed that Lactobacillus acidophilus KFRI342 (2 × 10 9 CFU) was able to reduce significantly the number of ACF in DMH-induced F344 rats, while Yamazaki et al (2000) showed that short and long term oral administration of L. casei Shirota lowered the number of large ACF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies showed the ability of numerous strains belonging to species L. acidophilus, L. casei and L. rhamnosus to either prevent or inhibit ACF formation (Rao, Sanders, Indranie, Simi, & Reddy, 1999;Verma & Shukla, 2013b). For instance Chang, Shim, Cha, Reaney, and Chee (2012) showed that Lactobacillus acidophilus KFRI342 (2 × 10 9 CFU) was able to reduce significantly the number of ACF in DMH-induced F344 rats, while Yamazaki et al (2000) showed that short and long term oral administration of L. casei Shirota lowered the number of large ACF.…”
Section: Discussionmentioning
confidence: 96%
“…β-Glucuronidase catalysed the hydrolysis of glucuronide conjugate which generated toxic and carcinogenic substances (Chipman, 1982), and β-glucosidase catalysed the hydrolysis of terminal non-reducing β-D-glucosides which induced the release of toxic colonic mutagens and carcinogens. Various studies using animal models showed the ability of other probiotic preparations to decrease the activity of those enzymes (Chang et al, 2012;Verma & Shukla, 2013b), and some clinical studies also demonstrated the same inhibitory effects (De Preter et al, 2007;Goldin & Gorbach, 1984). A study conducted by Asha and Gayathri (2012) demonstrated that mice fed with L. fermentum (2 × 10 8 CFU/g diet), L. plantarum (2 × 10 8 CFU/g diet) and vincristine alone decreased the activity of β-glucosidase by 70.4, 46.68 and 70.94% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relative abundance of the Lactobacillales order was decreased in colitic Il10 −/− and in AOM/ Il10 −/− mice, and in both cases, dietary curcumin restored this order to control levels. Lactobacillus strains have been used successfully in the CRC prevention in animal models 5154 , have been shown to exhibit significant antigenotoxicity 55 , and the Lactobacillus genus was shown to be associated with cell cycle arrest and induction of apoptosis in colon cancer cell lines 5657 . Although the results of systematic and well-controlled clinical studies in CRC prevention are not yet available, published reports suggest cautious optimism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relative abundance of the Lactobacillales order was decreased in colitic Il10 −/− and in AOM/Il10 −/− mice, and in both cases, dietary curcumin restored this order to control levels. Lactobacillus strains have been used successfully in the CRC prevention in animal models [51][52][53][54] , have been shown to exhibit significant antigenotoxicity 55 , and the Lactobacillus genus was shown to be associated with cell cycle arrest and induction of apoptosis in colon cancer cell lines 5657 . Although the results of systematic and wellcontrolled clinical studies in CRC prevention are not yet available, published reports suggest cautious optimism.…”
Section: Discussionmentioning
confidence: 99%